Pelatihan dalam Pembuatan Pupuk Bokashi pada Ibu-Ibu PKK: Meningkatkan Kreativitas dan Kesehatan Lingkungan - Anandita, Salsabila Putri; Utomo, Handika Ridho (Universitas Negeri Semarang, 2025)
This article discusses the bokashi fertilizer making training held for PKK (Family Welfare Empowerment) mothers as an effort to improve creativity and environmental health. This training aims to provide knowledge and practical skills in processing organic waste into useful fertilizer, while reducing the negative impact of waste on the environment. The results of the training showed that participants not only gained new skills, but also became more aware of the importance of organic waste management. By applying the knowledge gained, it is hoped that PKK mothers can actively contribute to maintaining environmental cleanliness and creating new economic opportunities through bokashi fertilizer production. This article emphasizes the importance of training as a tool for community empowerment in efforts to improve the quality of life and environmental health.